Kombinasi Aerobic Training Dengan Eksternal Diafragma Pacing Dalam Meningkatkan Ventilasi Pada PPOK: The Combination of Aerobic Training and External Diaphragm Pacing in Improving Ventilation in COPD Patients - N.D. Londong, Elisabeth; Santoso, Shelfi Dwi Retnani Putri; Paju, Wanto (Program Studi Keperawatan Waikabubak, Politeknik Kesehatan Kementerian Kesehatan Kupang, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a respiratory condition caused by air pollution and is one of the leading causes of morbidity and mortality worldwide. This condition results in air trapping/retention and impaired gas exchange, leading to symptoms such as dyspnea, coughing, excessive sputum production, and ventilation disturbances in COPD patients. Ventilation disturbances cause reduced energy reserves, making individuals unable to breathe adequately. Objective: To describe the implementation of a combination of aerobic training and external diaphragm pacing in improving ventilation in COPD patients. Methods: This case study used a descriptive method involving two respondents. The inclusion criteria were patients diagnosed with COPD, aged 60–70 years, fully conscious (compos mentis), hospitalized for at least three days, and experiencing mild respiratory function disorders. Nursing care and interventions included aerobic training exercises and diaphragm pacing implemented over three days. Results: After three days of nursing care, the respiratory rate of patient 1 decreased from 28 breaths/min to 21 breaths/min with an SpO2 of 98%, and the patient reported feeling relaxed and free from dyspnea. Similarly, patient 2’s respiratory rate decreased from 27 breaths/min to 22 breaths/min with an SpO2 of 99%, and the patient also reported no dyspnea and feeling relaxed. Conclusion: Aerobic training and diaphragm pacing effectively improve expiratory muscle function, ensuring sufficient oxygen supply to tissues. Recommendation: Aerobic training and diaphragm pacing should be practiced regularly to maintain heart and lung health..